Eccrine porocarcinoma mimicking a venous leg ulcer - Erdmann, Michael; Brauner, Kathrin; Bauerschmitz, Jürgen; Erfurt-Berge, Cornelia (International Wound Journal, 2016)
EVALuna2:19627

Gleichzeitiges Auftreten zweier malignomverdächtiger Hautveränderungen - Kaufmann, Matthias; Erdmann, Michael; Schliep, Stefan; Voskens, Caroline; Berking, Carola; Bauerschmitz, Jürgen (Die Dermatologie, 2024)
CRIS-Team Scopus Importer:2024-06-14

Multi-antigen imaging reveals inflammatory dc, adam17 and neprilysin as effectors in keloid formation - Rath, Mathias; Pitiot, Alain; Kirr, Michael; Fröhlich, Waltraud; Plosnita, Bianca; Schliep, Stefan; Bauerschmitz, Jürgen; Baur, Andreas; Ostalecki, Christian (International Journal of Molecular Sciences, 2021)
Keloid is an aberrant scarring process of the skin, characterized by excessive extracellular matrix synthesis and deposition. The pathogenesis of this prevalent cutaneous disorder is not fully understood; however, a persistent inflammatory process is observed. To obtain more insight into this process, we analyzed lesional, perilesional and healthy tissue using multi-antigen-analysis (MAA) in conjunction with a data mining approach. Here, we demonstrate that monocyte-derived inflammatory dendritic cells (CD1a+, CD11c+, CD14+) and activated CD4+ T lymphocytes (CD45 RO+) dominated the immune infiltration in keloids while associating with fibroblasts. In perilesional tissue, precursor immune cells were dominant in the perivascular area, suggesting that they were attracted by an immune process, potentially in the lesional area. Supporting this hypothesis, only in keloid lesions, high levels of ADAM10/17 and Neprilysin (CD10) were observed in both fibroblasts and leukocytes. The spatial proximity of these two cell types, which could be confirmed by image analysis only in lesional tissue, could be a potential factor leading to the activation of fibroblasts. Our findings provide new insight into the pathogenesis of keloid formation and reveal metalloproteinases as a target for therapeutical intervention.
CRIS-Team Scopus Importer:2021-09-10
Keywords: Dendritic cells; Multiplex imaging; Proteases; Scar; Single-cell analysis; Tumor biology; Tumor microenvironment

S2k guidelines for the therapy of pathological scars (hypertrophic scars and keloids) – Update 2020 - Nast, Alexander; Gauglitz, Gerd; Lorenz, Kerstin; Metelmann, Hans-Robert; Paasch, Uwe; Strnad, Vratislav; Weidmann, Michael; Werner, Ricardo Niklas; Bauerschmitz, Jürgen (Journal der Deutschen Dermatologischen Gesellschaft, 2020)
CRIS-Team Scopus Importer:2020-10-16

S2k-Leitlinie Therapie pathologischer Narben (hypertrophe Narben und Keloide) –Update 2020 - Nast, Alexander; Gauglitz, Gerd; Lorenz, Kerstin; Metelmann, Hans Robert; Paasch, Uwe; Strnad, Vratislav; Weidmann, Michael; Werner, Ricardo Niklas; Bauerschmitz, Jürgen (Journal der Deutschen Dermatologischen Gesellschaft, 2021)
CRIS-Team Scopus Importer:2021-02-26